Medical Rehabilitation Program for Knee Osteoarthritis: A Narrative Review - Refa Rahmaddiansyah; Riri Prima Yolanda; Rini Agustin (Faculty of Medicine, Universitas Andalas, 2024)
Osteoarthritis, a prevalent form of arthritis linked to bone degeneration, particularly affects the elderly population. In Indonesia, its prevalence rises with age, impacting various ethnic groups, notably women, and leading to substantial disability in individuals aged 65 and older. Vigilance is essential against potential complications like gastritis, bleeding, or kidney issues resulting from prolonged use of non-steroidal anti-inflammatory drugs (NSAIDs). The condition's pathophysiology involves joint aging, injuries, excessive use, genetic predisposition, obesity, and hormonal changes. Its clinical signs develop gradually but can accelerate due to injuries or joint strain, significantly reducing patient productivity and life quality. Managing osteoarthritis involves non-drug approaches like education, physical and exercise therapy, followed by medication and supportive devices. The treatment selection depends on severity and the number of affected joints, aiming to control pain, improve joint function, ease physical limitations, and hinder disease progression and complications. Prompt intervention with suitable modalities aligned with the patient's condition offers a favorable prognosis. Factors like muscle weakness, obesity, and depressive disorders can exacerbate osteoarthritis outcomes. Comprehensive management addressing these factors can significantly improve the prognosis and enhance the patient's quality of life.